Konten Kurikulum Akuntansi Perguruan Tinggi Dan Kesesuaiannya Dengan Standar Kompetensi Lulusan - Tasniem Fauzia; Afni, Zalida; Elfitri Santi (Akuntansi dan Manajemen, 2021)
Changing trends in business and finance have an impact on accounting learning and curriculum. This study aims to see how the college accounting curriculum produces competent graduates and their conformity with the IQF competency standards, the competencies needed to prepare graduates to enter the accounting profession and the competencies expected by users (employers). This study uses a mix-method with a sequential exploratory model (content analysis and descriptive statistical analysis). The results of this study show that colleges provide graduates with competencies in accounting, business, general competencies and other competencies that can support graduates' careers. The compatibility between graduates competencies based on the college accounting curriculum and the IQF competency standards has been appropriate, while the compatibility between graduates competencies with the professional organizations competency and user expectations competency has not been appropriate. In their curriculum, some college have included courses related to digital technology. We hoped there will be further harmonization and adjustment between the accounting curriculum and graduate competency standards to improve graduates work ability.